PENGARUH SUASANA CAFE, KUALITAS PELAYANAN CAFE, DAN HARGA TERHADAP KEPUASAN PELANGGAN - Ruagadi, Dinda Novelina (Universitas Nusantara PGRI Kediri, 2025)
This study analyzes the influence of cafe atmosphere, service quality, cafe price, and price on customer satisfaction. The method used was descriptive quantitative, with 40 respondents selected through purposive sampling. The research covered the variables of cafe atmosphere, cafe service quality, price, and customer satisfaction. The instrument was tested for validity and reliability. Data were collected through a questionnaire and analyzed using multiple linear regression, the classical assumption test, the simultaneous test (F test), the partial test (t test), and the coefficient of determination (R²) of 0.871. This indicates that the independent variables, cafe atmosphere, cafe service quality, and price, explain 87.1% of the variation in the dependent variable, customer satisfaction. Meanwhile, the remaining 12.9% is influenced by other factors not examined in this study. The results indicate that cafe atmosphere, service quality, cafe price, and price have a significant effect on customer satisfaction.